2012
DOI: 10.4049/jimmunol.1100136
|View full text |Cite
|
Sign up to set email alerts
|

The MC159 Protein from the Molluscum Contagiosum Poxvirus Inhibits NF-κB Activation by Interacting with the IκB Kinase Complex

Abstract: Molluscum contagiosum virus (MCV) causes persistent neoplasms in healthy and immunocompromised people. Its ability to persist likely is due to its arsenal of viral immune evasion proteins. For example, the MCV MC159 protein inhibits TNFR1-induced NF-κB activation and apoptosis. The MC159 protein is a viral FLIP and, as such, possesses two tandem death effector domains (DEDs). We show here that, in HEK293T cells, the expression of wild-type MC159 or a mutant MC159 protein containing the first DED (MC159 A) inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 51 publications
(104 reference statements)
5
51
0
Order By: Relevance
“…For example, within the context of a single FLIP, both DED1 and DED2 must be present for antiapoptosis function of MC159 (53,54,71). In contrast, MC159 DED1 is sufficient to inhibit NF-κB activation (41). Here, either DED1 or DED2 of MC159 is sufficient to inhibit IRF3 activation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, within the context of a single FLIP, both DED1 and DED2 must be present for antiapoptosis function of MC159 (53,54,71). In contrast, MC159 DED1 is sufficient to inhibit NF-κB activation (41). Here, either DED1 or DED2 of MC159 is sufficient to inhibit IRF3 activation.…”
Section: Resultsmentioning
confidence: 99%
“…All luciferase activities were measured as relative light units using a BioTek luminometer and the Dual Luciferase Reporter Assay System (Promega). Relative luciferase activity ratios were calculated as described previously (41). In some instances, a portion of each cellular lysate from luciferase assays was analyzed for protein expression by immunoblotting, using the antiserum indicated under each immunoblot in the figures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that overexpression of MC159 inhibits NF-B activation by several stimuli, including death receptor stimulation or MyD88 overexpression (16)(17)(18), and that MC159 acts at the level of the inhibitor of B kinase (IKK) complex by interacting with the IKK␥ subunit (also called NF-B essential modulator [NEMO]) (18). However, it has also been shown that MC159 can activate NF-B: transient expression of MC159 in human Jurkat or 293 cells led to a significantly increased NF-B activity, and the ambivalent effect appeared to depend on MC159 and RIP1 expression levels (19).…”
mentioning
confidence: 99%